(untitled) (Plant Tissue Culture and Biotechnology, 2015)
Three Bangladeshi barley genotypes viz. BARI barley?1, 3 and 6 were selected for this study to evaluate the efficiency of callus induction and plant regeneration. The effect of five doses of AgNO3 singly, and combined with amino acids (Lproline, L?glutamine) on callus induction and plant regeneration efficiency was evaluated using BARI barley?3 and 6. The maximum values of callus induction were recorded at 49.20 and 32.66% for BARI barley?6 and 3, respectively when 2.0 mg/l AgNO3 and 200 mg/l L?glutamine were added to the callus induction medium. Moreover, plant regeneration remarkably increased on MS + 1.0 mg/l BAP + 1.5 mg/l AgNO3 + 150 mg/l L?glutamine as 37.20% in BARI barley?6 and 16.13% in BARI barley?3. For rooting AgNO3 singly affect positively, whereas negative influence was observed in combinations with any amino acids. However, by using AgNO3 and amino acids, around < 4, < 27 and < 5 fold increase in callus induction were obtained. Regeneration and rooting were also found to increase considerably. Plant Tissue Cult. & Biotech. 25(1): 37-50, 2015 (June)